Growth performance, microbial and hemato-biochemical profile, and organs histology of broiler chickens fed diets supplemented with a seasoning named Jumbo Cube as source of monosodium glutamate (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: this study was conducted in order to assess the effects of dietary Jumbo Cube as source of Monosodium Glutamate (MSG) on production performances of broiler chickens.Materials and methods: 320 day-old Ross 308 broiler chicks were randomly divided into five groups of 64 chicks each. Negative and positive control groups were fed on basal diet with no supplement (R0-) and 1 gm of antibiotic (R0+) respectively and the 3 others groups were fed on diets supplemented with the quantities of Jumbo cube containing 1 mg, 2 mg and 4 mg of MSG/Kg of feed. Feed intake (FI), feed conversion ratio (FCR), weight gain (WG), blood parameters and intestinal microbial counts were evaluated.Results: Results revealed that feeding broilers with Jumbo Cube as MSG source significantly (P